Glyphosate Market in Thailand: Opportunities and Challenges - Suvittawat, Adisak (Information Management and Business Review, 2014)
The purpose of this study is to find out the opportunities and challenges of the glyphosate market in Thailand, which is affected by product registration laws, demand, supply, and product positioning and price segmentation. The methodology of this study consists of primary data from 2013 market surveys both at dealer and farmer levels and secondary data collected from 2009-2013 using descriptive methods. The results show that herbicides, fungicides and insecticides werethetop three kinds of imported pesticides used for crop production in Thailand from 2009-2013. Herbicide imports increased fromUS291.83 million (MUSD) and 53,615.20 tons in 2009, to 352.93 MUSD and 60,231.52 tons in 2012. Glyphosate was the leading pesticide import in 2012, in cost and amount, at 88.13 MUSD and 19,721 tons. Many glyphosate brands compete in a price-segmented market. Monsanto’s Roundup brand is the most expensive, at 18.12-18.75USD per four liters (/4 L). Brands such as Ecomax are priced in the medium range, at13.75-16.25 USD/4 L. This segment has other brands too, such as Market and Popular, and they are sold in different regions. Other brands are in the lowest price range, at 1.25-13.45 USD/4 L. Thailand has not yet approved genetically modified (GM) crops that can tolerate glyphosate, so the market for glyphosate is very limited at the moment. If the Thai government approves GM crops, the glyphosate market will have more opportunity for growth.